Association of severity of depression, paroxetine use and markers of liver damage with QT interval duration in patients with alcohol dependence - Vukadinović Stojanović, Sanja; Stojanović, Zlatan (Vojnosanitetski pregled, 2021)
Background/Aim. Patients suffered from chronic alcoholic disease very often have depression and cardiomyopathy. Treatment with several antidepressants is associated with prolonged QT interval, ventricular arrhythmias and sudden death. The aim of this study was to investigate the relation between the severity of depression, serum levels of gamma-glutamyl transferase (GGT), as a marker of liver damage, and the possible influence of paroxetine use on duration of QT interval in patient who started treatment of chronic alcoholic dependence. Methods. The study included 147 male patients (older than 18 years of age) suffering from alcohol addiction, who were also diagnosed with depressive disorder on the basis of DSM-IV criterion and positive Hamilton Rating Scale for Depression (HRSD) at the beginning of hospitalization. Out of total number of patients, 49 were randomly selected to be treated with antidepressant paroxetine at a dose of 20 mg once daily during 20 days. The global QTc interval was automatically determined. Results. By applying the generalised linear model, the statistically significant positive correlation between the length of QTc interval and serum values of GGT, that is, intensity of alcoholism (p = 0.002) and values of the HRSD score, that is, intensity of depression (p = 0.021) was established in the sample of 147 depressed alcoholic patients before the application of paroxetine. In spite of the vulnerability of patients due to the heart damage and the liver dysfunction arising from alcohol consumption, as well as altered patients' drugs metabolism, no elongation of QTc interval resulting from the application of paroxetine was established. The length of QTc interval 20 days after paroxetine administration was 401.43 ms and before paroxetine administration it was 403.31 ms. The difference in QTc interval length (after and before paroxetine administration) was ΔQTc = -1.88 ms (p = 0.524). Conclusion. The results indicated that the severity of depression and GGT serum levels positively correlated with the length of QT interval. On the other hand, paroxetine after 20 days of usage did not prolong QT interval.
Keywords: alcoholism; alcohol-induced disorders; depression; comorbidity; long QT syndrome; paroxetine